Pengaruh Kualitas Layanan, Harga dan Inovasi Digital Terhadap Kepuasan Pengguna Jasa Pelabuhan (Studi Kasus Pada PT. Prima Multi Terminal) - Rizna Anggia (Fakultas Ekonomi Universitas Al-Azhar Medan, 2026)
The development of the port service industry requires companies to continuously enhance their competitiveness through service quality, pricing strategies, and digital innovation. This study aims to examine and analyze the influence of service quality, price, and digital innovation on user satisfaction at PT Prima Multi Terminal. The research employed a quantitative approach with a survey design, involving 75 respondents of service users. Data analysis was conducted using multiple linear regression to test the partial and simultaneous effects of the independent variables on user satisfaction. The results indicate that service quality, price, and digital innovation have a positive and significant effect, both partially and simultaneously, on user satisfaction. This finding suggests that improving service quality, setting competitive prices, and implementing continuous digital innovation are essential factors in increasing customer satisfaction. In conclusion, these three factors are key determinants of user satisfaction, and future research is recommended to explore other external factors such as customer trust and loyalty.